2020
DOI: 10.1158/1538-7445.am2020-6251
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 6251: Blood brain barrier opening by TTFields: a future CNS drug delivery strategy

Abstract: Introduction: Although a number of effective drugs are available to treat central nervous system (CNS) disorders, their ability to breach the tight regulation of the blood brain barrier (BBB) still remains a major challenge. Recently, the use of tumor treating fields (TTFields) has become an effective treatment approach for glioblastoma. Furthermore, its combination with chemotherapy significantly improved overall patient survival. Nonetheless, how TTFields could affect the BBB has not yet been studied. Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Thus, it is possible that loss-of-function mutations in PTEN could potentiate the inhibition of microtubule polymerization and mitotic spindle apparatus assembly that are known to result from TTFields exposure. Ultimately, future investigations should provide insights towards a unified understanding of the mechanism of action of TTFields-induced cytoskeletal changes, cancer cell membrane permeabilization, and permeabilization of the blood-brain barrier [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that loss-of-function mutations in PTEN could potentiate the inhibition of microtubule polymerization and mitotic spindle apparatus assembly that are known to result from TTFields exposure. Ultimately, future investigations should provide insights towards a unified understanding of the mechanism of action of TTFields-induced cytoskeletal changes, cancer cell membrane permeabilization, and permeabilization of the blood-brain barrier [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…The blood-brain barrier is a vital structure to maintain the stability of the internal environment of brain. Chemotherapy for brain tumors usually lacks of effectiveness because most chemotherapeutic drugs are difficult to penetrate the blood-brain barrier [ 75 ]. In vivo experiments show that Evans Blue, TRITC-dextran, and magnetic resonance contrast agent Gd-DTPA increase in the brain [ 75 78 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy for brain tumors usually lacks of effectiveness because most chemotherapeutic drugs are difficult to penetrate the blood-brain barrier [ 75 ]. In vivo experiments show that Evans Blue, TRITC-dextran, and magnetic resonance contrast agent Gd-DTPA increase in the brain [ 75 78 ]. Meanwhile, in vitro experiments showed that Claudin-5 and Occludin translocation in capillary endothelial cells [ 76 , 79 ] points out that TTFields increases the permeability of the blood-brain barrier.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations